PENERAPAN SISTEM AKUNTANSI DIGITAL TERHADAP SIKLUS PENJUALAN DAN PENERIMAAN KAS DI KLINIK - Yulianti Safitri (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The development of information technology has driven a significant transformation in accounting management, especially through the implementation of digital accounting information systems that can improve the efficiency and accuracy of recording sales and cash receipt transactions. This study aims to examine how the implementation of digital accounting information systems can improve work efficiency and its impact on overall business development. The method used is a narrative review that analyzes scientific literature, books and journals related to digital accounting systems and operational efficiency. The results of the study show that digital accounting information systems enable transaction processes to be faster and more accurate, reduce recording errors and accelerate financial reporting. This increased work efficiency provides real-time data that is very useful for management in making strategic decisions that strengthen overall business development. The implementation of digital accounting information systems not only improves operational effectiveness but also plays an important role as a strategic tool in supporting business growth and competitiveness in the digital era.